Height and weight-adjusted intrathecal 0.5% hyperbaric Bupivacaine for elective cesarean section: an outcome analysis in a rural Nepal tertiary centre - Khapung, Robin; Basnyat, Subi; Thapa, Nabin; Giri, Praveen Kumar; Bhatterai, Ramesh; Bhandari, Jeetendra; Shrestha, Prerana; Banjade, Subika; Pandey, Alan; Adhikari, Apil; Limbu, Poshan Samser; Silwal, Shirish; et al. (Journal of General Practice and Emergency Medicine of Nepal, 2025)
Introduction: Spinal anesthesia with 0.5% hyperbaric bupivacaine is preferred for cesarean section(CS) but often causes maternal hypotension with potential fetal effects. Using Harten’s chart to dose based on height and weight may limit block height and reduce hypotension. We compared fixed-dose and adjusted regimens. Method: This prospective observational study at Karnali Academy of Health Sciences (Aug–Dec 2022) included 58 term singleton ASA II women undergoing elective CS. Intrathecal 0.5% hyperbaric bupivacaine was given as either fixed dose (11 mg) or Harten’s chart–calculated dose. Primary outcome was change in mean arterial pressure; secondary outcomes were systolic blood pressure, heart rate, block characteristics, vasopressor use, and adverse effects. Significance was P < 0.05. Result: Adjusted-dose group received lower median intrathecal dose than fixed-dose group (9 mg [IQR 8.5–9.5] vs 11 mg; P<0.001), with slower onset to T6 (median 4 min [IQR 4–5] vs 2 min [IQR 2–4]; P<0.001) and lower 20-min maximum sensory level (median T5 vs T3; P<0.001). No adjusted-dose patients reached T2, compared with 6(20.7%) in fixed-dose group (P=0.023). Maternal hypotension was less frequent with dose adjustment (17.2% vs 31%; P=0.357), with comparable reductions in MAP and SBP (ΔMAP 26.0 [20.0–34.0] vs 26.0 [23.0–41.0] mmHg, P=0.290; ΔSBP 26.0 [17.0–36.0] vs 32.0 [23.0–46.0] mmHg, P=0.134). Fewer adjusted-dose patients required mephentermine (10.3% vs 41%; P=0.015), bradycardia and vomiting occurred only in the fixed-dose group. Conclusion: Height and weight-adjusted intrathecal bupivacaine provides adequate anesthesia with less maternal hypotension and lower block height than standard dose.